PROSPECTS FOR THE DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIP IN THE SPHERE OF VOCATIONAL EDUCATION FOR RECOVERY OF THE ECONOMY OF UKRAINE (Innovative professional education, 2023)
The priority for the development of vocational (vocational and technical) education in the wartime and post war periods is to preserve and increase human capital to restore the state's economy. The article analyses the problematic aspects of the effectivedevelopment of public-private partnerships in the field of vocational (vocational and technical) education: the lack of a coordinated system of interaction between state and non-state parties; imperfect legislation; low motivation of partners to invest in the development of vocational (vocational and technical) education, etc. Prospects for the development of public-private partnerships in the field of vocational education and training are identified: creation of a modern regulatory framework; introduction of motivational mechanisms for non-state parties to invest in the development vocational (vocational and technical) education; introduction of global investment educational projects; creation of innovative vocational education institutions to ensure lifelong learning, etc.
Keywords: vocational (vocational and technical) education, public-private partnership, human capital